1998
DOI: 10.1046/j.1471-4159.1998.71020723.x
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase Is Increased in the Brains of Transgenic Mice Expressing the C‐Terminal Fragment (CT100) of the β‐Amyloid Protein Precursor of Alzheimer's Disease

Abstract: Acetylcholinesterase (AChE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 30 publications
7
58
0
Order By: Relevance
“…4C). AChE exhibits complex structural polymorphism (39) with a molecular form pattern which is altered in AD (18,66,70). Accordingly, we found that the major G 4 ).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…4C). AChE exhibits complex structural polymorphism (39) with a molecular form pattern which is altered in AD (18,66,70). Accordingly, we found that the major G 4 ).…”
Section: Resultsmentioning
confidence: 79%
“…Despite an overall decrease in the AD brain, the activity of AChE is increased around the amyloid plaques (42,78). This may be a direct consequence of amyloid deposition, since A␤ peptides influence AChE levels in cell cultures (25,69) and in the brains of transgenic mice that produce human A␤ (70). Conversely, AChE may play a role in A␤ fibrillogenesis (27,60).…”
mentioning
confidence: 99%
“…TghCTF99/B6 mice express hCTF99(V717F), thus it is possible that histological and behavioral changes observed in Tg-hCTF99/ B6 mice are due to an as-yet-unidentified toxic effect of hCTF99(V717F). Among the previously generated transgenic mouse lines expressing CTFs described in Introduction, three lines had been designed to express mutant forms of CTFs, C100(V -I) (Araki et al, 1994), C100(V -F) (Sberna et al, 1998), and C99(I -F) (Rutten et al, 2003), although these transgenic lines do not show any obvious AD-like pathogenesis. In particular, transgenic mice expressing C100(V -F) (Sberna et al, 1998) carry a mutation essentially identical to that of Tg-hCTF99/B6 mice but showed no clear phenotype.…”
Section: The Roles Of Bctf99 In Ad-related Pathogenesismentioning
confidence: 99%
“…Among the previously generated transgenic mouse lines expressing CTFs described in Introduction, three lines had been designed to express mutant forms of CTFs, C100(V -I) (Araki et al, 1994), C100(V -F) (Sberna et al, 1998), and C99(I -F) (Rutten et al, 2003), although these transgenic lines do not show any obvious AD-like pathogenesis. In particular, transgenic mice expressing C100(V -F) (Sberna et al, 1998) carry a mutation essentially identical to that of Tg-hCTF99/B6 mice but showed no clear phenotype. Given the severe phenotypes shown by Tg-hCTF99/B6 mice, the absence of a phenotype in their CTFexpressing line may have been due to a low level of transgene expression or a blocking effect due to unidentified genetic backgrounds in a hybrid background.…”
Section: The Roles Of Bctf99 In Ad-related Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation